Bioactive compounds from Polygonatum genus as anti-diabetic agents with future perspectives. (15th May 2023) - Shi, Yan; Si, Dun; Chen, Donghong; Zhang, Xinfeng; Han, Zhigang; Yu, Qiang; Liu, Jingjing; Si, Jinping
Highlights: The traditional and modern applications of Polygonatum in diabetes were systematically summarized. The safety and effectiveness of polysaccharides, flavonoids and saponins from Polygonatum genus were assessed. New pathways for the prevention and treatment of diabetes using Polygonatum genus were proposed. Abstract: Diabetes mellitus (DM) is one of the most serious health problems worldwide. Species in the genus Polygonatum are traditional food and medicinal plants, which play an important role in controlling blood glucose. In this reveiw, we systematically summarized the traditional and modern applications of the genus Polygonatum in DM, focused on the material bases of polysaccharides, flavonoids and saponins. We highlighted their mechanisms of action in preventing obese diabetes, improving insulin resistance, promoting insulin secretion, regulating intestinal microecology, inhibiting advanced glycation end products (AGEs) accumulation, suppressing carbohydrate digestion and obsorption and modulating gluconeogenesis. Based on the safety and efficacy of this 'medicinal food' and its utility in the prevention and treatment of diabetes, we proposed a research and development program that includs diet design (supplementary food), medical nutrition therapy and new drugs, which could provide new pathways for the use of natural plants in prevention and treatment of DM.